2001
DOI: 10.1046/j.1528-1157.2001.33100.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Convulsions After Consuming a Large Amount of Gingko Nuts

Abstract: Summary:We report a 36-year-old woman, without any past or family histories of epilepsy, who presented frequent vomiting and generalized convulsions. About 4 h before the convulsion, she had consumed ∼70-80 gingko nuts, seeds of Gingko biloba, in an attempt to improve her health. It is important to know that convulsion may be induced if a large amount of gingko nuts is consumed. The neurotoxicity of gingko nuts, particularly their convulsion-inducing effect, should be recognized. Key Words: Gingko biloba-Gingk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 5 publications
(7 reference statements)
0
30
0
Order By: Relevance
“…As known from in vivo studies, 4′-O-methylpyridoxine (MPN) competes with vitamin B 6 , which is a cofactor of glutamate decarboxylase; as a consequence, MPN indirectly inhibits the activity of this enzyme resulting in a decrease of the γ-aminobutyric acid (GABA) level in brain, which predisposes to convulsions. 9,17,18 The study reported in this paper describes a case of ginkgo poisoning which occurred in Switzerland in a 23-months-old boy, where the association with the ingestion of ginkgo seeds was confirmed by measuring biomarkers both in blood and urine.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…As known from in vivo studies, 4′-O-methylpyridoxine (MPN) competes with vitamin B 6 , which is a cofactor of glutamate decarboxylase; as a consequence, MPN indirectly inhibits the activity of this enzyme resulting in a decrease of the γ-aminobutyric acid (GABA) level in brain, which predisposes to convulsions. 9,17,18 The study reported in this paper describes a case of ginkgo poisoning which occurred in Switzerland in a 23-months-old boy, where the association with the ingestion of ginkgo seeds was confirmed by measuring biomarkers both in blood and urine.…”
Section: Introductionmentioning
confidence: 85%
“…7,8 Even though they are infrequent, clinical cases of ginkgo seed poisoning show severe symptoms, including tonic or clonic convulsion, vomiting, irritability and loss of consciousness. [7][8][9] Poisoning by ginkgo seeds is due to the neurotoxic compound 4′-O-methylpyridoxine (MPN), which is chemically related to vitamin B 6 and interfere with its biosynthesis, metabolism and function. The chemical structures of MPN and vitamin B 6 are reported in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ginkgo biloba comprises a variety of biologically active chemical constituents, including components that induce [47,48] and inhibit [49][50][51][52] seizure activity. The principal antiepileptic compounds in the ginkgo plant are ginkgolides and bilobalide.…”
Section: Ginkgo Biloba (Yinxingye)mentioning
confidence: 99%
“…This herbal tea is believed to be safe, however, it can be toxic when taken in excessive doses with some of the constituents of hyssop oil thought to aggravate seizures [103]. Ginkgo biloba nuts [104] and Chinese ginseng [105] have also been suggested to be proconvulsant. Ginkgo seeds contain a seizure-promoting neurotoxin called 4-methoxypyridoxine (MPN) [106] (also termed as "Ginkgotoxin") that indirectly inhibits GABA A formation.…”
Section: Safety Issues On the Use Of Botanicalsmentioning
confidence: 99%